The Return to College, Marriage, and Intergenerational Mobility - Eric D. Gould (Institute of Labor Economics (IZA), 2023)
This paper examines the idea that the increasing return to college is reducing intergenerational mobility by differentially impacting the investments in children by parents across education groups. A larger return to college will create stronger incentives to invest in children by parents with more education, if educated parents have a comparative advantage in producing human capital in children. Given the importance of a two-parent household on childhood development, marital status is a critical investment decision that parents consider. Relative to less-educated mothers, the analysis shows that educated mothers in states with a larger increase in the return to education are more likely to be married, less likely to divorce, have a more educated spouse, and own more valuable houses. Their children also have relatively higher test scores in 8th grade and rates of college completion. These results are consistent with the increasing return to college differentially affecting the incentives for parental investments in children, which in turn, creates greater disparities in childhood conditions and reduces intergenerational mobility in education.
Keywords: I24; I26; J12; J24; 330; marriage; inequality; return to college